High-strength fireproof door core material and preparation method thereof
Through the preparation method of composite heat insulation materials and flame retardant adhesives, the heat insulation and strength problems of fire-proof door core materials under extreme fire conditions are solved, high-strength, long-term heat insulation and flame retardant performance are improved, and the reliability of fire-proof doors is enhanced.
Patent Information
- Application Number
- CN202510764723.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-10
- Publication Date
- 2025-08-22
- Estimated Expiration
- 2045-06-10
AI Technical Summary
The existing fire door core materials have fast thermal insulation performance and weak anti-explosion impact capabilities under extreme fire conditions. Traditional materials are prone to structural disintegration due to high temperatures, affecting the reliability of fire partitions.
The preparation method of composite heat insulation materials and flame retardant adhesives is adopted to prepare high-strength fire-resistant door core materials through mixing, spraying and curing processes, and the synergistic effect of alumina and silicone structures is used to improve heat insulation and flame retardant performance and enhance the binding force of the material.
Effectively improve the flame retardant performance, thermal insulation performance and strength of the fire-resistant door core material. The nano-scale porous structure of alumina and silicone reduces heat radiation transmission. The flame retardant adhesive releases non-combustible gas during fire, forming a carbonized layer to prevent the spread of the fire and enhance the overall strength.
Smart Images

Figure BDA0005441236760000041
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fire door core material preparation, and particularly relates to a high-strength fire door core material and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization and the large-scale development of high-rise buildings and large public facilities, building fire safety has become a major global issue. As a core component of a building's fire separation system, fire doors play a crucial role in preventing the spread of fire, slowing the spread of smoke, and buying valuable time for evacuation and fire rescue efforts. In recent years, fires have become increasingly frequent worldwide, particularly in high-rise buildings. Due to the rapid spread of fire, limited escape windows, and significant property damage, these issues have placed increasingly stringent demands on the performance of fire doors. Traditional fire door core materials, primarily made of inorganic materials such as expanded perlite, vermiculite, and aluminum silicate fiber, meet basic fire resistance requirements. However, these materials exhibit limited mechanical properties, rapid thermal insulation degradation, and weak resistance to blast shock. Especially under extreme fire conditions, these core materials are susceptible to structural collapse, insulation failure, and even deformation and detachment of the door due to high temperatures, seriously threatening the reliability of fire compartments. Therefore, there is an urgent need to develop a new fire door core material that combines high strength, flame retardancy, and long-lasting thermal insulation.
[0003] Patent CN108275951A discloses a high-strength green fire-resistant door core and its preparation method. The high-strength green fire-resistant door core comprises the following components in the following mass ratios: 400-800 parts aluminate cement, 300-450 parts ceramsite, 2-5 parts fiber, 1-2 parts sodium polyacrylate granules, and 64-160 parts water. When mixed with aluminate cement, ceramsite, and fiber, the sodium polyacrylate granules absorb a large amount of water, expanding to several dozen to several hundred times their original volume. After drying, the primary product releases water and shrinks, forming numerous closed pores. The ceramsite has a honeycomb interior, characterized by low density, low thermal conductivity, and high strength. When combined with aluminate cement, this can significantly enhance the impact resistance of the fire-resistant door core. However, the thermal insulation, flame retardancy, and strength of the fire-resistant door core produced by this method still require improvement. Summary of the Invention
[0004] The purpose of the present invention is to provide a high-strength fire door core material and a preparation method thereof, which are used to solve the technical problems of poor heat insulation, flame retardancy and strength of fire door core materials in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a high-strength fireproof door core material, comprising the following steps:
[0007] Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add the pretreated composite thermal insulation material, expanded perlite, and glass fiber into a blender and mix to obtain a mixture.
[0008] Step 2: Add the flame retardant adhesive to the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
[0009] Preferably, in the step one, the amount ratio of the pretreated composite thermal insulation material, expanded perlite and glass fiber is (50-70) g: (15-23) g: (10-18) g; in the step two, the amount ratio of the flame retardant adhesive and the mixture is (26-38) g: (78-92) g.
[0010] Preferably, the method for preparing the composite thermal insulation material comprises the following steps:
[0011] Q1: 1-Bromododecane and dimethylaminoethanol were added to a container, followed by acetone, and the mixture was heated and stirred for reaction. After the reaction was completed, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain a product. Alumina particles were added to a container containing deionized water, stirred at room temperature, and the product, urea, and hydrochloric acid were then added. The mixture was stirred continuously to obtain a mixed solution 1.
[0012] Q2: Methyltrimethoxysilane and dimethoxydimethylsilane are added to the mixed solution 1, stirred and mixed, sealed, and added to an oven. Subsequently, ethanol is added to the container, and the container is continued to be placed in the oven, dried, and calcined to obtain a composite thermal insulation material.
[0013] In the above process, 1-bromododecane and dimethylaminoethanol undergo a substitution reaction to obtain a product, which can then be adsorbed on the surface of alumina particles through electrostatic action to obtain a mixed solution 1. Methyltrimethoxysilane and dimethoxydimethylsilane are then added to the mixed solution 1 to undergo a hydrolysis reaction, which then undergoes a condensation reaction on the surface of the alumina to form a substance containing a siloxane bond. Finally, after calcination, a composite thermal insulation material with a three-dimensional structure is obtained.
[0014] Preferably, in Q1, the amount ratio of 1-bromododecane, dimethylaminoethanol and acetone is (20-31.2) g: (11.21-15.42) g: (60-80) mL, the heating and stirring reaction temperature is 60-64°C, and the reaction time is 6-8 h; the amount ratio of alumina particles, deionized water, product, urea and hydrochloric acid is (0.08-0.32) g: (17-20) mL: (0.3-0.5) g: (10-15) g: (7-9) μL, the stirring time at room temperature is 5-8 h, and the continued stirring time is 30-45 min.
[0015] Preferably, in Q2, the amount ratio of methyltrimethoxysilane, dimethoxydimethylsilane and mixed solution 1 is (6-8) mL: (1.91-2.03) mL: (24-29) mL, the stirring mixing time is 2-4 h, the oven temperature is 80-85 ° C, after adding ethanol, the oven temperature is maintained at 80-83 ° C for 48-52 h, and then maintained at 60-65 ° C for 70-75 h, and the ethanol is replaced every 8-10 h. The calcination temperatures are 200 ° C, 400 ° C, and 600 ° C, respectively, and the heating rate is 5 ° C / min.
[0016] Preferably, the method for preparing the flame retardant adhesive comprises the following steps:
[0017] S1: slowly adding a morpholine aqueous solution to a mixture of cyanuric chloride and acetone under low temperature, stirring at low temperature to react, then adding a sodium carbonate aqueous solution dropwise, continuing to stir at low temperature to react, and after the reaction is completed, washing and drying to obtain intermediate 1;
[0018] S2: Add 80% hydrazine hydrate to intermediate 1, heat and stir to react, and after the reaction is complete, cool, filter, wash, and dry to obtain intermediate 2;
[0019] S3: Add intermediate 2 to a container containing dimethylacetamide, then add dicyclohexylmethane diisocyanate and dibutyltin dilaurate, and heat to react under argon atmosphere to obtain a prepolymer. Add terminal hydroxyl polydimethylsiloxane to dimethylacetamide, and then add it dropwise to the prepolymer, heat to react, and after the reaction is completed, dry to obtain a flame retardant adhesive.
[0020] In the above process, the synthetic reaction formula of the flame retardant adhesive is as follows:
[0021]
[0022] The results of mass spectrometry analysis of intermediate 1 were: m / z: 234.01 (100.0%), 236.00 (63.9%), 238.00 (10.3%), 235.01 (7.7%), 237.01 (4.9%), 235.00 (1.5%); the results of mass spectrometry analysis of intermediate 2 were: m / z: 226.13 (100.0%), 227.13 (10.6%).
[0023] Preferably, in S1, the amount ratio of the morpholine aqueous solution, cyanuric chloride, acetone and sodium carbonate aqueous solution is (25-32) mL: (6.12-6.93) g: (140-160) mL: (35-40) mL, the concentration of the morpholine aqueous solution is 0.23 g / mL, the low temperature environment temperature is -18 to -20°C, the low temperature stirring reaction temperature is -18 to -20°C, the time is 1-2h, the concentration of the sodium carbonate aqueous solution is 0.13 g / mL, and the low temperature stirring reaction temperature is continued to be -18 to -20°C, and the time is 1-2h.
[0024] Preferably, in S2, the usage ratio of the intermediate 1 and 80% hydrazine hydrate is (1.5-2.3) g: (90-110) mL, the heating and stirring reaction temperature is 70-73° C., and the reaction time is 10-14 h.
[0025] Preferably, in S3, the molar ratio of intermediate 2 and dicyclohexylmethane diisocyanate is (0.8-1.2): (0.82-1.21), the heating reaction temperature is 60-80°C, the reaction time is 1-2h, the amount ratio of terminal hydroxyl polydimethylsiloxane, dimethylacetamide and prepolymer is (0.43-0.52)g: (10-12)mL: (8.01-10.23)g, the heating reaction temperature is 50-60°C, and the reaction time is 1-4h.
[0026] The high-strength fireproof door core material is prepared by adopting the preparation method of the high-strength fireproof door core material.
[0027] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0028] 1. In the process of preparing the core material of the fire door, the present invention adds a composite thermal insulation material and a flame retardant adhesive, which can effectively improve the flame retardancy, fire resistance, thermal insulation and strength of the core material of the fire door.
[0029] 2. The present invention adds the prepared composite thermal insulation material to the core material of the fire door, which can effectively improve its thermal insulation performance, fire resistance and strength. The synergistic effect of alumina and silicone structure can effectively prevent the transfer of heat. The nano-scale porous structure can reduce the transfer of heat radiation and improve its thermal insulation performance. At the same time, the synergistic effect of silicone and alumina can enhance the fire resistance. The silicone structure can also enhance the bonding force between alumina particles and improve strength.
[0030] 3. The present invention adds the prepared flame retardant adhesive to the core material of the fire door, which can effectively improve its flame retardant properties and strength. The triazine structure contained in the flame retardant adhesive can release non-combustible gas and dilute the concentration of combustible gas when a fire occurs. It can also form a carbonized layer on the surface of the material to prevent the spread of fire and improve the flame retardant properties of the core material of the fire door. The active groups contained in the adhesive can be combined with the components in the core material of the fire door through chemical bonds to improve the bonding strength, make the various parts of the core material more tightly bonded, and improve its overall strength. DETAILED DESCRIPTION
[0031] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0032] Example 1: This example discloses a method for preparing a composite thermal insulation material, comprising the following steps:
[0033] Q1: 25.6 g of 1-bromododecane and 13.32 g of dimethylaminoethanol were added to a container, followed by the addition of 70 mL of acetone, and the mixture was heated and stirred at 62°C for 6 h. After the reaction, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain the product. 0.2 g of alumina particles was added to a container containing 18.5 mL of deionized water, and the mixture was stirred at room temperature for 6 h. Subsequently, 0.4 g of the product, 12.5 g of urea, and 8 μL of 1 mol / L hydrochloric acid were added, and the mixture was stirred for 30 min to obtain a mixed solution 1.
[0034] Q2: Add 7 mL of methyltrimethoxysilane and 1.97 mL of dimethoxydimethylsilane to 26.5 mL of mixed solution 1, stir and mix for 4 hours, seal, and add to an 80°C oven. Then add ethanol to the container and continue to place it in the oven. The oven temperature is maintained at 80°C for 48 hours, and then maintained at 60°C for 72 hours. The ethanol is replaced every 8-10 hours and calcined. The calcination temperatures are 200°C, 400°C, and 600°C, respectively, and the heating rate is 5°C / min to obtain a composite thermal insulation material.
[0035] This embodiment discloses a method for preparing a flame retardant adhesive, comprising the following steps:
[0036] S1: Slowly add 28.5 mL of a 0.23 g / mL morpholine aqueous solution to a mixture of 6.52 g of cyanuric chloride and 150 mL of acetone at -20°C, and stir at -20°C for 2 h. Then, dropwise add 37.5 mL of a 0.13 g / mL sodium carbonate aqueous solution, and continue stirring at -20°C for 2 h. After the reaction, wash and dry to obtain intermediate 1.
[0037] S2: Add 100 mL of 80% hydrazine hydrate to 1.9 g of intermediate 1, heat and stir at 72°C for 12 h. After the reaction, cool, filter, wash, and dry to obtain intermediate 2;
[0038] S3: Add 2.38 g of intermediate 2 to a container containing 10 mL of dimethylacetamide, then add 2.62 g of dicyclohexylmethane diisocyanate and 0.02 g of dibutyltin dilaurate, and heat the reaction at 75°C under an argon atmosphere for 2 h to obtain a prepolymer. Add 0.47 g of terminal hydroxyl polydimethylsiloxane to 11 mL of dimethylacetamide, and then add it dropwise to 9.11 g of the prepolymer, and heat the reaction at 60°C for 4 h. After the reaction is completed, dry to obtain a flame retardant adhesive.
[0039] This embodiment discloses a method for preparing a high-strength fireproof door core material, comprising the following steps:
[0040] Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add 6.0 kg of the pretreated composite thermal insulation material, 1.9 kg of expanded perlite, and 1.4 kg of glass fiber into a blender and mix to obtain a mixture;
[0041] Step 2: Add 3.2 kg of flame retardant adhesive to 8.5 kg of the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
[0042] Example 2: This example discloses a method for preparing a composite thermal insulation material, comprising the following steps:
[0043] Q1: 20 g of 1-bromododecane and 11.2 g of dimethylaminoethanol were added to a container, followed by 80 mL of acetone, and the mixture was heated and stirred at 62°C for 6 h. After the reaction, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain the product. 0.08 g of alumina particles was added to a container containing 17 mL of deionized water, and the mixture was stirred at room temperature for 6 h. Subsequently, 0.5 g of the product, 10 g of urea, and 7 μL of 1 mol / L hydrochloric acid were added, and stirring was continued for 30 min to obtain a mixed solution 1.
[0044] Q2: Add 6 mL of methyltrimethoxysilane and 1.91 mL of dimethoxydimethylsilane to 29 mL of mixed solution 1, stir and mix for 4 hours, seal, and add to an 80°C oven. Then add ethanol to the container and continue to place it in the oven. The oven temperature is maintained at 80°C for 48 hours, and then maintained at 60°C for 72 hours. The ethanol is replaced every 8-10 hours and calcined. The calcination temperatures are 200°C, 400°C, and 600°C, respectively, and the heating rate is 5°C / min to obtain a composite thermal insulation material.
[0045] This embodiment discloses a method for preparing a flame retardant adhesive, comprising the following steps:
[0046] S1: Slowly add 25 mL of a 0.23 g / mL morpholine aqueous solution to a mixture of 6.12 g of cyanuric chloride and 140 mL of acetone at -20°C, and stir at -20°C for 2 h. Then, add dropwise 35 mL of a 0.13 g / mL sodium carbonate aqueous solution, and continue stirring at -20°C for 2 h. After the reaction, wash and dry to obtain intermediate 1.
[0047] S2: Add 110 mL of 80% hydrazine hydrate to 1.5 g of intermediate 1, heat and stir at 72°C for 12 h. After the reaction, cool, filter, wash, and dry to obtain intermediate 2.
[0048] S3: 1.81 g of intermediate 2 was added to a container containing 10 mL of dimethylacetamide, followed by the addition of 2.15 g of dicyclohexylmethane diisocyanate and 0.02 g of dibutyltin dilaurate. The mixture was heated at 75°C for 2 h under an argon atmosphere to obtain a prepolymer. 0.43 g of hydroxy-terminated polydimethylsiloxane was added to 10 mL of dimethylacetamide, and then added dropwise to 8.01 g of the prepolymer. The mixture was heated at 60°C for 4 h. After the reaction was completed, the mixture was dried to obtain a flame-retardant adhesive.
[0049] This embodiment discloses a method for preparing a high-strength fireproof door core material, comprising the following steps:
[0050] Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add 5.0 kg of the pretreated composite thermal insulation material, 1.5 kg of expanded perlite, and 1.8 kg of glass fiber into a blender and mix to obtain a mixture;
[0051] Step 2: Add 2.6 kg of flame retardant adhesive to 7.8 kg of the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
[0052] Example 3: This example discloses a method for preparing a composite thermal insulation material, comprising the following steps:
[0053] Q1: 31.2 g of 1-bromododecane and 15.42 g of dimethylaminoethanol were added to a container, followed by the addition of 60 mL of acetone, and the mixture was heated at 62°C with stirring for 6 h. After the reaction, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain the product. 0.32 g of alumina particles was added to a container containing 20 mL of deionized water, and the mixture was stirred at room temperature for 6 h. Subsequently, 0.3 g of the product, 15 g of urea, and 9 μL of 1 mol / L hydrochloric acid were added, and stirring was continued for 30 min to obtain a mixed solution 1.
[0054] Q2: Add 8 mL of methyltrimethoxysilane and 2.03 mL of dimethoxydimethylsilane to 24 mL of mixed solution 1, stir and mix for 4 hours, seal, and add to an 80°C oven. Then add ethanol to the container and continue to place it in the oven. The oven temperature is maintained at 80°C for 48 hours, and then maintained at 60°C for 72 hours. The ethanol is replaced every 8-10 hours and calcined. The calcination temperatures are 200°C, 400°C, and 600°C, respectively, and the heating rate is 5°C / min to obtain a composite thermal insulation material.
[0055] This embodiment discloses a method for preparing a flame retardant adhesive, comprising the following steps:
[0056] S1: Slowly add 32 mL of a 0.23 g / mL morpholine aqueous solution to a mixture of 6.93 g of cyanuric chloride and 160 mL of acetone at -20°C, and stir at -20°C for 2 h. Then, add dropwise 40 mL of a 0.13 g / mL sodium carbonate aqueous solution, and continue stirring at -20°C for 2 h. After the reaction, wash and dry to obtain intermediate 1.
[0057] S2: Add 90 mL of 80% hydrazine hydrate to 2.3 g of intermediate 1, heat and stir at 72°C for 12 h. After the reaction, cool, filter, wash, and dry to obtain intermediate 2;
[0058] S3: Add 2.72 g of intermediate 2 to a container containing 10 mL of dimethylacetamide, then add 2.17 g of dicyclohexylmethane diisocyanate and 0.02 g of dibutyltin dilaurate, and heat the reaction at 75°C under an argon atmosphere for 2 h to obtain a prepolymer. Add 0.47 g of terminal hydroxyl polydimethylsiloxane to 11 mL of dimethylacetamide, and then add it dropwise to 9.11 g of the prepolymer, heat the reaction at 60°C for 4 h, and after the reaction is completed, dry to obtain a flame retardant adhesive.
[0059] This embodiment discloses a method for preparing a high-strength fireproof door core material, comprising the following steps:
[0060] Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add 7.0 kg of the pretreated composite thermal insulation material, 2.3 kg of expanded perlite, and 1.0 kg of glass fiber into a blender and mix to obtain a mixture;
[0061] Step 2: Add 3.8 kg of flame retardant adhesive to 9.2 kg of the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
[0062] Example 4: This example discloses a method for preparing a composite thermal insulation material, comprising the following steps:
[0063] Q1: 22.3 g of 1-bromododecane and 12.11 g of dimethylaminoethanol were added to a container, followed by the addition of 65 mL of acetone, and the mixture was heated at 62°C with stirring for 6 h. After the reaction, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain the product. 0.12 g of alumina particles was added to a container containing 18 mL of deionized water, and the mixture was stirred at room temperature for 6 h. Subsequently, 0.35 g of the product, 11 g of urea, and 7.5 μL of 1 mol / L hydrochloric acid were added, and stirring was continued for 30 min to obtain a mixed solution 1.
[0064] Q2: Add 6.5 mL of methyltrimethoxysilane and 1.94 mL of dimethoxydimethylsilane to 25 mL of mixed solution 1, stir and mix for 4 hours, seal, and add to an 80°C oven. Then add ethanol to the container and continue to place it in the oven. The oven temperature is maintained at 80°C for 48 hours, and then maintained at 60°C for 72 hours. The ethanol is replaced every 8-10 hours and calcined. The calcination temperatures are 200°C, 400°C, and 600°C, respectively, and the heating rate is 5°C / min to obtain a composite thermal insulation material.
[0065] This embodiment discloses a method for preparing a flame retardant adhesive, comprising the following steps:
[0066] S1: Slowly add 26 mL of a 0.23 g / mL morpholine aqueous solution to a mixture of 6.27 g of cyanuric chloride and 145 mL of acetone at -20°C, and stir at -20°C for 2 h. Then, add dropwise 36 mL of a 0.13 g / mL sodium carbonate aqueous solution, and continue stirring at -20°C for 2 h. After the reaction, wash and dry to obtain intermediate 1.
[0067] S2: Add 95 mL of 80% hydrazine hydrate to 1.7 g of intermediate 1, heat and stir at 72°C for 12 h. After the reaction, cool, filter, wash, and dry to obtain intermediate 2;
[0068] S3: 1.99 g of intermediate 2 was added to a container containing 10 mL of dimethylacetamide, followed by the addition of 2.38 g of dicyclohexylmethane diisocyanate and 0.02 g of dibutyltin dilaurate. The mixture was heated at 75°C for 2 h under an argon atmosphere to obtain a prepolymer. 0.47 g of hydroxy-terminated polydimethylsiloxane was added to 11 mL of dimethylacetamide, and then added dropwise to 9.11 g of the prepolymer. The mixture was heated at 60°C for 4 h. After the reaction was completed, the mixture was dried to obtain a flame-retardant adhesive.
[0069] This embodiment discloses a method for preparing a high-strength fireproof door core material, comprising the following steps:
[0070] Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add 5.5 kg of the pretreated composite thermal insulation material, 1.8 kg of expanded perlite, and 1.2 kg of glass fiber into a blender and mix to obtain a mixture;
[0071] Step 2: Add 2.8 kg of flame retardant adhesive to 8.1 kg of the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
[0072] Comparative Example 5: This embodiment discloses a method for preparing a composite thermal insulation material, comprising the following steps:
[0073] Q1: 28.7 g of 1-bromododecane and 14.78 g of dimethylaminoethanol were added to a container, followed by the addition of 75 mL of acetone, and the mixture was heated at 62°C with stirring for 6 h. After the reaction, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain the product. 0.28 g of alumina particles was added to a container containing 19 mL of deionized water, and the mixture was stirred at room temperature for 6 h. Subsequently, 0.45 g of the product, 14 g of urea, and 8.5 μL of 1 mol / L hydrochloric acid were added, and stirring was continued for 30 min to obtain a mixed solution 1.
[0074] Q2: Add 7.5 mL of methyltrimethoxysilane and 1.99 mL of dimethoxydimethylsilane to 28 mL of mixed solution 1, stir and mix for 4 hours, seal, and add to an 80°C oven. Then add ethanol to the container and continue to place it in the oven. The oven temperature is maintained at 80°C for 48 hours, and then maintained at 60°C for 72 hours. The ethanol is replaced every 8-10 hours and calcined. The calcination temperatures are 200°C, 400°C, and 600°C, respectively, and the heating rate is 5°C / min to obtain a composite thermal insulation material.
[0075] This embodiment discloses a method for preparing a flame retardant adhesive, comprising the following steps:
[0076] S1: Slowly add 31 mL of a 0.23 g / mL morpholine aqueous solution to a mixture of 6.73 g of cyanuric chloride and 155 mL of acetone at -20°C, and stir at -20°C for 2 h. Then, add dropwise 38 mL of a 0.13 g / mL sodium carbonate aqueous solution, and continue stirring at -20°C for 2 h. After the reaction, wash and dry to obtain intermediate 1.
[0077] S2: Add 105 mL of 80% hydrazine hydrate to 2.1 g of intermediate 1, heat and stir at 72°C for 12 h. After the reaction, cool, filter, wash, and dry to obtain intermediate 2.
[0078] S3: Add 2.47 g of intermediate 2 to a container containing 10 mL of dimethylacetamide, then add 3.01 g of dicyclohexylmethane diisocyanate and 0.02 g of dibutyltin dilaurate, and heat the reaction at 75°C under an argon atmosphere for 2 h to obtain a prepolymer. Add 0.47 g of terminal hydroxyl polydimethylsiloxane to 11 mL of dimethylacetamide, and then add it dropwise to 9.11 g of the prepolymer, heat the reaction at 60°C for 4 h, and after the reaction is completed, dry to obtain a flame retardant adhesive.
[0079] This embodiment discloses a method for preparing a high-strength fireproof door core material, comprising the following steps:
[0080] Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add 6.5 kg of the pretreated composite thermal insulation material, 2.1 kg of expanded perlite, and 1.6 kg of glass fiber into a blender and mix to obtain a mixture;
[0081] Step 2: Add 3.6 kg of flame retardant adhesive to 8.8 kg of the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
[0082] Comparative Example 1: Compared with Example 2, in Comparative Example 1, during the preparation of the high-strength fire-resistant door core material, no composite thermal insulation material was added, and other conditions remained unchanged.
[0083] Comparative Example 2: Compared with Example 2, in the process of preparing the high-strength fire-resistant door core material in Comparative Example 2, sodium silicate is used instead of the flame retardant adhesive, and other conditions remain unchanged.
[0084] The high-strength fire-resistant door core materials prepared according to Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests. The combustion performance of the samples was tested according to GB 8624-2012, the fire resistance of the samples was tested according to GB / T 7633-2008, and the strength and thermal insulation properties of the samples were tested according to JC / T 2568-2020. The test results are shown in Table 1:
[0085] Table 1
[0086] project Combustion performance grade Refractory time / min Compressive strength / MPa Thermal conductivity / [W / (m·K)] Example 1 A 72 0.68 0.024 Example 2 A 69 0.66 0.031 Example 3 A 66 0.63 0.028 Example 4 A 68 0.64 0.029 Example 5 A 69 0.62 0.026 Comparative Example 1 A 54 0.54 0.12 Comparative Example 2 B1 67 0.56 0.026
[0087] The test results in Table 1 show that the fire-resistant door core materials prepared according to Examples 1-5 have excellent flame retardancy, fire resistance, thermal insulation, and strength. A comparison of Comparative Example 1 with Examples 1-5 shows that the use of composite thermal insulation materials can effectively improve the fire resistance, thermal insulation, and strength of the fire-resistant door core materials. A comparison of Comparative Example 2 with Examples 1-5 shows that the use of flame-retardant adhesives can effectively improve the flame retardancy and strength of the fire-resistant door core materials.
[0088] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
[0089] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to specific embodiments. Obviously, many modifications and variations are possible based on the contents of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing a high-strength fireproof door core material, characterized in that: The following steps are involved: Step 1: Dry the composite thermal insulation material, then spray an ethanol solution containing a silane coupling agent, and simultaneously dry the expanded perlite. Then, add the pretreated composite thermal insulation material, expanded perlite, and glass fiber into a blender and mix to obtain a mixture. Step 2: Add the flame retardant adhesive to the mixture, stir, then add it to the mold, vibrate to exhaust, cure, and cut to obtain the high-strength fire door core material.
2. The method for preparing a high-strength fireproof door core material according to claim 1, characterized in that: In the step 1, the usage ratio of the pretreated composite thermal insulation material, expanded perlite and glass fiber is (50-70) g: (15-23) g: (10-18) g; in the step 2, the usage ratio of the flame retardant adhesive and the mixture is (26-38) g: (78-92) g.
3. The method for preparing a high-strength fireproof door core material according to claim 1, characterized in that: The preparation method of the composite thermal insulation material comprises the following steps: Q1: 1-Bromododecane and dimethylaminoethanol were added to a container, followed by acetone, and the mixture was heated and stirred for reaction. After the reaction was completed, the mixture was cooled, filtered under reduced pressure, recrystallized, and dried in vacuo to obtain a product. Alumina particles were added to a container containing deionized water, stirred at room temperature, and the product, urea, and hydrochloric acid were then added. The mixture was stirred continuously to obtain a mixed solution 1. Q2: Methyltrimethoxysilane and dimethoxydimethylsilane are added to the mixed solution 1, stirred and mixed, sealed, and added to an oven. Subsequently, ethanol is added to the container, and the container is continued to be placed in the oven, dried, and calcined to obtain a composite thermal insulation material.
4. The method for preparing a high-strength fireproof door core material according to claim 3, characterized in that: In Q1, the usage ratio of 1-bromododecane, dimethylaminoethanol and acetone is (20-31.2) g: (11.21-15.42) g: (60-80) mL; the usage ratio of alumina particles, deionized water, product, urea and hydrochloric acid is (0.08-0.32) g: (17-20) mL: (0.3-0.5) g: (10-15) g: (7-9) μL.
5. The method for preparing a high-strength fireproof door core material according to claim 3, characterized in that: In the Q2, the usage ratio of methyltrimethoxysilane, dimethoxydimethylsilane and mixed solution 1 is (6-8) mL: (1.91-2.03) mL: (24-29) mL.
6. The method for preparing a high-strength fireproof door core material according to claim 1, characterized in that: The preparation method of the flame retardant adhesive, The following steps are involved: S1: slowly adding a morpholine aqueous solution to a mixture of cyanuric chloride and acetone under low temperature, stirring at low temperature to react, then adding a sodium carbonate aqueous solution dropwise, continuing to stir at low temperature to react, and after the reaction is completed, washing and drying to obtain intermediate 1; S2: Add 80% hydrazine hydrate to intermediate 1, heat and stir to react, and after the reaction is complete, cool, filter, wash, and dry to obtain intermediate 2; S3: Add intermediate 2 to a container containing dimethylacetamide, then add dicyclohexylmethane diisocyanate and dibutyltin dilaurate, and heat to react under argon atmosphere to obtain a prepolymer. Add terminal hydroxyl polydimethylsiloxane to dimethylacetamide, and then add it dropwise to the prepolymer, heat to react, and after the reaction is completed, dry to obtain a flame retardant adhesive.
7. The method for preparing a high-strength fireproof door core material according to claim 6, characterized in that: In S1, the dosage ratio of the morpholine aqueous solution, cyanuric chloride, acetone and sodium carbonate aqueous solution is (25-32) mL: (6.12-6.93) g: (140-160) mL: (35-40) mL, the concentration of the morpholine aqueous solution is 0.23 g / mL, and the concentration of the sodium carbonate aqueous solution is 0.13 g / mL.
8. The method for preparing a high-strength fireproof door core material according to claim 6, characterized in that: In the S2, the usage ratio of the intermediate 1 and 80% hydrazine hydrate is (1.5-2.3) g: (90-110) mL.
9. The method for preparing a high-strength fireproof door core material according to claim 6, characterized in that: In S3, the molar ratio of intermediate 2 to dicyclohexylmethane diisocyanate is (0.8-1.2): (0.82-1.21), and the amount ratio of hydroxy-terminated polydimethylsiloxane, dimethylacetamide and prepolymer is (0.43-0.52) g: (10-12) mL: (8.01-10.23) g.
10. A high-strength fireproof door core material is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Perlite thermal insulation board making technology
CN105000861A
Preparation method for phenolic aldehyde plate thermal insulation material for building exterior wall
CN108690321A
Method of and system for forming a fire door core
US20020100996A1
Fire-resistant article and method of manufacture
US4695494A
Gypsum building product
US5171366A